Manoscritti inclassificabili della Vita S. Pauli Monachi Thebaei di San Girolamo - Degórski, Bazyli (Vox Patrum, 2019)
Manuscripts which cannot be included in any of the families of the manuscript tradition of St. Jerome’s Vita Sancti Pauli Primi Eremitae, examined by John Frank Cherf, O.S.B., are the following: Bernensis Lat. 111, Bruxellensis 64, Cameracensis 864 (767), Dresdensis A 62 cod. D, Laurentianus pl. 19, cod. 16, Matritensis 10007, Parisinus Lat. 3784, Parisinus Lat. 5314, Parisinus Lat. 5385, Parisinus Lat. 9741, Vaticanus Lat. 5411, Vaticanus Lat. 7014, Vaticanus Barberinianus Lat. 586, Basilicanus A. 2, Vindobonensis Lat. 420 and Vindobonensis S. Mariae ad Scotos 409 (324). To these can be added the following ones, found by the author: Iagellonicus Cracoviensis 2265 AA XII 9, Casanatensis Codex 718 (B.I.3), Lateranensis Codex A. 79, Farfensis 5 (270), Sessorianus 5 (XXIX), Vallicellanus Tomus III, Vaticanus Lat. 600, Vaticanus Lat. 5257, Vaticanus Lat. 9309, Vaticanus Lat. 13393, Vaticanus Barberinianus Lat. 469, Vaticanus Urbinas Lat. 396, Basilicanus A. 4.